Task shifting interpersonal counseling for depression: a pragmatic randomized controlled trial in primary care - Matsuzaka, Camila T. (BMC Psychiatry, 2017)
BACKGROUND: Task shifting approaches (rational redistribution of tasks among health workforce teams) to train lay professionals to assist with integrating mental health treatment in primary care has been recommended to close the mental health treatment gap for depression in low- and middle-income countries. This study aims to examine the a new model for depression care in a low-resource environment compared to enhanced treatment at usual (E-TAU). METHODS: We trained non-specialist community health workers (local lay employees of the public health system) to provide Interpersonal Counseling (IPC) to treat depressive symptoms in the Brazilian, São Paulo city, family health strategy (FHS). We conducted a randomized controlled trial involving 86 patients with a current major depressive disorder or dysthymia (based on DSM-IV) recruited from an FHS clinic. Participants were randomized to IPC intervention (n = 43) or E-TAU (n = 43). Participants allocated to IPC received 3–4 sessions provided by community health workers; research psychologists followed the E-TAU participants to facilitate their referral to specialized mental health care within the public system. Reduction of depressive symptoms was assessed using the Hamilton Rating Scale (HDRS-17) and the Patient Health Questionnaire (PHQ-9); minor psychiatric symptomatology (including depression, anxiety and somatoform symptoms) were measured using the Self Reporting Questionnaire (SRQ); and functioning was measured by the Clinical Global Impression Scale over a 2-month period. RESULTS: Intention-to-treat analysis showed significant improvement on symptoms for both groups over 2 months, without significant differences between them. Per-protocol analysis showed significant better HDRS-17 outcomes for the IPC group. CONCLUSIONS: Training non-specialist community health workers in low- and middle-income countries to provide IPC could be a successful strategy in reducing the burden of depression and also potentially a low-cost and effective alternative to specialist-led services that might not be possible in low income settings. TRIAL REGISTRATION: Brazilian Clinical Trials, number RBR-5qhmb5 (trial url: http://www.ensaiosclinicos.gov.br/rg/RBR-5qhmb5/), retrospectively registered after May 1, 2013.